2007
DOI: 10.1212/01.wnl.0000256367.70365.e0
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray analysis identifies candidate regions and genes in unexplained mental retardation

Abstract: We could identify novel microimbalances as the probable cause of mental retardation in 10% of patients with unclear etiology. The gene content of the microimbalances was found to correlate with phenotype severity. Precise breakpoint analyses allowed the identification of deleted genes presumably causing mental retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 33 publications
(30 reference statements)
4
61
1
Order By: Relevance
“…68 Copy number variation (CNV), including deletion and duplication, translocation, inversion of chromosomes, has been identified in some individuals with autism. 14,69 In fact, Engels et al 70 showed a direct association between the severity of physical anomalies and the chance to find mutant CNVs. The results of this meta-analysis suggest that MPAs in autism are, at least in part, related to the risk of developing the disease and that these MPAs may therefore precede the clinical onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…68 Copy number variation (CNV), including deletion and duplication, translocation, inversion of chromosomes, has been identified in some individuals with autism. 14,69 In fact, Engels et al 70 showed a direct association between the severity of physical anomalies and the chance to find mutant CNVs. The results of this meta-analysis suggest that MPAs in autism are, at least in part, related to the risk of developing the disease and that these MPAs may therefore precede the clinical onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…FISH was performed using BlueFISH tile BAC probes RP11-12D3 and RP11-29K14 from the deleted region according to manufacturer's instructions (BlueGnome Ltd, Cambridge, United Kingdom) and as published previously. 2 Figure 2b). qPCR analyses of patient 3 and her parents confirmed the deletion in patient 3 and demonstrated its de novo occurrence.…”
Section: Patientmentioning
confidence: 97%
“…4 Causative familial copy number changes with reduced penetrance have also been described, however. 2,5,6 Several patients with similar copy number changes and a similar clinical presentation are, therefore, needed to allow reliable genotype-phenotype correlation. Recently, some recurrent rearrangements have been described for, amongst others, chromosomal regions 1q21.1, 5 1q41q42, 7 2p15p16.1, 8 16p13.11, 9,10 18q21 11 -13 and 17q21.31.…”
Section: Introductionmentioning
confidence: 99%
“…De novo microdeletions detected by genome-wide array analysis at 19p13 have been reported in few patients, [1][2][3][4][5] all of whom had malformations and mental retardation (MR). We present the detailed clinical and molecular description of two new cases (cases 1 and 3) with partially overlapping 19p13 microdeletions identified by investigating patients with syndromic MR using array comparative genomic hybridization (aCGH).…”
Section: Introductionmentioning
confidence: 99%